Apatite Formation from Amorphous Calcium Phosphate and Mixed Amorphous Calcium Phosphate/Amorphous Calcium Carbonate. Issue 35 (27th July 2016) - Ibsen, Casper J. S.; Chernyshov, Dmitry; Birkedal, Henrik
Abstract: Crystallization from amorphous phases is an emerging pathway for making advanced materials. Biology has made use of amorphous precursor phases for eons and used them to produce structures with remarkable properties. Herein, we show how the design of the amorphous phase greatly influences the nanocrystals formed therefrom. We investigate the transformation of mixed amorphous calcium phosphate/amorphous calcium carbonate phases into bone‐like nanocrystalline apatite using in situ synchrotron X‐ray diffraction and IR spectroscopy. The speciation of phosphate was controlled by pH to favor HPO4 2− . In a carbonate free system, the reaction produces anisotropic apatite crystallites with large aspect ratios. The first formed crystallites are highly calcium deficient and hydrogen phosphate rich, consistent with thin octacalcium phosphate (OCP)‐like needles. During growth, the crystallites become increasingly stoichiometric, which indicates that the crystallites grow through addition of near‐stoichiometric apatite to the OCP‐like initial crystals through a process that involves either crystallite fusion/aggregation or Ostwald ripening. The mixed amorphous phases were found to be more stable against phase transformations, hence, the crystallization was inhibited. The resulting crystallites were smaller and less anisotropic. This is rationalized by the idea that a local phosphate‐depletion zone formed around the growing crystal until it was surrounded by amorphous calcium carbonate, which stopped the crystallization. Abstract : Let it grow ! The kinetics of the apatite formation from hydrogen‐phosphate‐rich amorphous calcium phosphate with and without added carbonate is studied by a range of in situ techniques. Seeds of hydrogen‐phosphate‐rich apatite, akin to a few layers of octacalcium phosphate, form first and are overgrown by more stoichiometric apatite (see figure).